Vitamin E (Journal of Parents and Teachers, 2016)
The following article deals with the project “Vitamin E” which is based on an educational program for Primary and Secondary school. This project bases on improving the student’s attitude and aptitude that they would be enterprising people. In each stage, there are some activities whose objective is the student’s training through how a person can be an enterprising throughout their own initiatives.
Keywords: education; Vitamin E; enterprising; training; initiative; creativity.